Chronic ethanol intake promotes double gluthatione S-transferase transforming growth factor-alpha-positive hepatocellular lesions in male Wistar rats - Pires, Paulo Wagner [UNESP]; Furtado, Kelly Silva [UNESP]; Justullin, Luis Antonio [UNESP]; Rodrigues, Maria Aparecida Marchesan [UNESP]; Felisbino, Sergio Luis [UNESP]; Barbisan, Luis Fernando [UNESP] (Blackwell Publishing, 2008)
The chronic ethanol intake influence on the gluthatione S-transferase (GST-P) and transforming growth factor alpha (TGF-alpha) expression in remodeling/persistent preneoplastic lesions (PNLs) was evaluated in the resistant hepatocyte model. Male Wistar rats were allocated into five groups: G1, non-treated, fed water and chow ad libitum; G2, non-treated and pair-fed chow (restricted to match that of G3 group) and a maltodextrin (MD) solution in tap water (matched ethanol-derived calories); G3, fed 5% ethanol in drinking water and chow ad libitum; G4, diethylnitrosamine (DEN, 200 mg/kg, body weight) plus 200 parts per million of 2-acetylaminofluorene (2-AAF) for 3 weeks and pair-fed chow (restricted to match that of G5 group) and an MD solution in tap water (matched ethanol-derived calories); G5, DEN/2-AAF treatment, fed ethanol 5% and chow ad libitum. All animals were subjected to 70% partial hepatectomy at week 3 and sacrificed at weeks 12 or 22, respectively. Liver samples were collected for histological analysis or immunohistochemical expression of GST-P, TGF-alpha and proliferating cell nuclear antigen or zymography for matrix metalloproteinases-2 and -9. At the end of ethanol treatment, there was a significant increase in the percentage of liver area occupied by persistent GST-P-positive PNLs, the number of TGF-alpha-positive PNLs and the development of liver tumors in ethanol-fed and DEN/2-AAF-treated groups (G5 versus G4, P < 0.001). In addition, ethanol feeding led to a significant increase in cell proliferation mainly in remodeling and persistent PNLs with immunoreactivity for TGF-alpha at week 22 (P < 0.001). Gelatinase activities were not altered by ethanol treatment. The results demonstrated that ethanol enhances the selective growth of PNL with double expression of TGF-alpha and GST-P markers.